SIMULATION OF THE TRANSITIONAL REGIME OF THE MOLDOVAN POWER UNDER STATIC STABILITY - Postolaty V.M.; Golub I.V. (Problems of the Regional Energetics)
The paper presents the outcome of the Moldovan power system static stability modeling and analysis, considering the operation in parallel with the Ukrainian power system and the established operation regimes. The analysis includes verification of the reserve of static stability and definition of the static stability limits for a given operation mode, and the determination of the power system stability domain of the controlled system nodes. Parameters used for the analysis are the active power flows via controlled sections and the voltage levels at the controlled system nodes. Two options of Moldovan power system scheme are considered: a single-circuit transit Dniester HPP - Balti - Straseni – Chisinau 330kV and a double-circuit transit. Studies have shown that the implementation of the double-circuit transit would lead to better static stability parameters and lower power system losses. The analysis has been carried out based on the power system stability.